"Cadeira", by José Saramago : an example of revolutionary writing and perspective - Sílvia Amorim (Études romanes de Brno, 2025)
The short story 'Cadeira', published in the collection Objecto Quase [The Lives of Things] (1978), is part of a series of texts which, as well as illustrating the post-25 April break in José Saramago's career, evoke the challenges of the transition from dictatorship to democracy, drawing attention to this key moment in the country's history. The collapse of Salazar's dictatorship is evoked through unconventional narrative and stylistic strategies, allowing us to measure the impact of the Revolution on the work and to observe the revolution taking place in the writing itself. One of the most significant aspects of the subversion introduced by the text lies in the relearning of a critical, subversive and lucid vision as a bastion against the reduction of the human being to a mere object.